Effects of curing program on mechanical behavior and water absorption of DGEBA/TETa epoxy network. Issue 5 (30th January 2013) - Dang, D. Nguyen; Cohendoz, S.; Mallarino, S.; Feaugas, X.; Touzain, S.
Abstract Water uptake in organic coatings remains an interesting challenge for fundamental and applied researches because chemical, physical, and mechanical properties are concerned. The polymer network, which is affected by the curing program, is a key factor for water absorption. In this work, an epoxy network based on diglycidyl ether of bisphenol A and a hardener triethylentetramine was cured at different temperatures: below Tg (protocol 1) and above Tg (protocol 2). DMA, Differential Scanning Calorimetry (DSC), and FT‐IR measurements showed that both protocols allow to obtain totally cured networks. However, DSC and DMA results revealed that both cured networks present different levels of homogeneity, depending on the different curing conditions, which affect the free volume and the activation volume associated with visco‐elastic properties. The mechanical properties of free films and water sorption behaviors were investigated as function of cured conditions. It was found that protocol 1‐cured networks present higher mechanical properties and was less affected by water ingress than protocol 2‐cured systems, leading to better barrier properties. These results highlight the influence of the curing program onto the heterogeneous distribution of the epoxy network. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013